Development of an Active Packaging Film Based on a Methylcellulose Coating Containing Murta (Ugni Molinae Turcz) Leaf Extract - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (Springer New York LLC, 2016)
A new active packaging film based on murta leaf extract was elaborated. The extract was incorporated into a methylcellulose layer which was coated on a low-density polyethylene (LDPE) film. Its antioxidant effectivity, antimicrobial activity, and physicochemical properties were evaluated. The active film was able to keep its antimicrobial and antioxidant properties for at least 60 days. During this time, the growth of Listeria (L.) innocua was reduced by 2 log cycles and free radical formation could be inhibited by about 90 % for films stored under light and dark conditions. The active coating on the LDPE film did not affect the thermal and water vapor transmission properties; however, slight changes in the mechanical, color, and optical properties were observed. Finally, a sensory analysis showed that active coating did not change the flavor and odor properties of a fatty food packed inside the active material. This suggests that this active packaging film could be used to extend the shelf-life of packaged food. © 2015, Springer Science+Business Media New York.
Keywords: Active packaging; Antimicrobial; Antioxidant; Murta; Methylcellulose; Coating